(untitled) (International Journal of Social Research & Innovation, 2021)
The aim of this narrative enquiry was to explore the transition experiences of Maldivian teenagers as they transition from GCSE to Advanced Level Studies. Ten recent alumni of a higher secondary school in Male’ were selected based on purposive sampling to represent a wide range of experiences and challenges. Data was collected in 2018, using one on one, face-to-face, semi-structured interviews, and focus group discussions with boys and girls separately. This paper chronicles their transition experiences in four inter-dependent domains (1) preparedness, (2) fitting in, making friends and belonging, (3) personal grit, and formal and informal support available to meet the higher demands of advanced level studies, and (4) intense pressures the students experienced due to the social structural forces and inequalities which underline their higher secondary education experience as they work toward competitive scholarships for higher studies. Poverty, living away from home communities, lack of effective communication between parents and children, and lack of supportive mentoring relationships between teachers and students negatively influenced the transition experience. Poverty, lack of time management and independent study skills were the most important factors in failure to succeed. The findings of this study have implications for policy level change to ensure higher secondary school students are provided the support required to succeed in their studies.